PENGARUH MODEL QUANTUM TEACHING DISERTAI FLASHCARD TERHADAP HASIL BELAJAR SISWA PADA SUBMATERI SISTEM TRANSPORTASI - Yusniarni, Nur; Ningsih, Kurnia; Ariyati, Eka (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to knew the influence of quantum teaching of learning model with flash card on learning outcomes at VIII grade SMPN 3 Pontianak in the sub material transport system in living organisms. This research was using quasi experimental with nonequivalent control group design. The population is whole of VIII SMP which consist of nine classes. The samples were VIII F (as experimental class) and VIII I (as control class). The instrument that was multiple choices consisted of 20 items. Based on the research result, the average of posttest result of experimental class was 17,09, and the control class was 11,37. At U Mann-Whitney test was Zcount < Ztable (-6,01 < -1,96) which shows that there are differences of study result between the students that taught by quantum teaching of learning model with flash card and conventional of learning model. Based on the effect size result was 1,60 with the high category, which means that quantum teaching of learning model with flash card gave influence 44,52% toward the study result in the sub material transport system in living organisms. Keyword: learning outcomes, quantum teaching with flash card